Internet cognitive behavioural therapy for mixed anxiety and depression: a randomized controlled trial and evidence of effectiveness in primary care. Issue 12 (18th February 2013) - Newby, J. M.; Mackenzie, A.; Williams, A. D.; McIntyre, K.; Watts, S.; Wong, N.; Andrews, G.
Abstract : Background: Major depressive disorder (MDD) and generalized anxiety disorder (GAD) have the highest co-morbidity rates within the internalizing disorders cluster, yet no Internet-based cognitive behavioural therapy (iCBT) programme exists for their combined treatment. Method: We designed a six-lesson therapist-assisted iCBT programme for mixed anxiety and depression. Study 1 was a randomized controlled trial (RCT) comparing the iCBT programme ( n = 46) versus wait-list control (WLC; n = 53) for patients diagnosed by structured clinical interview with MDD, GAD or co-morbid GAD/MDD. Primary outcome measures were the Patient Health Questionnaire nine-item scale (depression), Generalized Anxiety Disorder seven-item scale (generalized anxiety), Kessler 10-item Psychological Distress scale (distress) and 12-item World Health Organization Disability Assessment Schedule II (disability). The iCBT group was followed up at 3 months post-treatment. In study 2, we investigated the adherence to, and efficacy of the same programme in a primary care setting, where patients ( n = 136) completed the programme under the supervision of primary care clinicians. Results: The RCT showed that the iCBT programme was more effective than WLC, with large within- and between-groups effect sizes found (>0.8). Adherence was also high (89%), and gains were maintained at 3-month follow-up. In study 2 in primary care, adherence to the iCBT programme was low (41%), yet effect sizes were large (>0.8). Of the non-completers, 30% experienced benefit. Conclusions: Together, the results show that iCBT is effective and adherence is high in research settings, but there is a problem of adherence when translated into the 'real world'. Future efforts need to be placed on developing improved adherence to iCBT in primary care settings.